2007
DOI: 10.1111/j.1469-8137.2007.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for substantial aerobic methane emission by terrestrial plants: a 13C‐labelling approach

Abstract: Summary The results of a single publication stating that terrestrial plants emit methane has sparked a discussion in several scientific journals, but an independent test has not yet been performed. Here it is shown, with the use of the stable isotope 13C and a laser‐based measuring technique, that there is no evidence for substantial aerobic methane emission by terrestrial plants, maximally 0.3% (0.4 ng g−1 h−1) of the previously published values. Data presented here indicate that the contribution of terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 22 publications
7
156
5
Order By: Relevance
“…Several studies have reported opposite results that no measurable CH 4 release from plants was detected (Beerling et al, 2008;Bowling et al, 2009;Dueck et al, 2007;Kirschbaum and Walcroft, 2008;Nisbet et al, 2009;Smeets et al, 2009;Takahashi et al, 2012). One potential explanation for the absence of CH 4 emissions is that the CH 4 produced was consumed by endophytic methanotrophs.…”
Section: Uncertainties and Limitationsmentioning
confidence: 85%
“…Several studies have reported opposite results that no measurable CH 4 release from plants was detected (Beerling et al, 2008;Bowling et al, 2009;Dueck et al, 2007;Kirschbaum and Walcroft, 2008;Nisbet et al, 2009;Smeets et al, 2009;Takahashi et al, 2012). One potential explanation for the absence of CH 4 emissions is that the CH 4 produced was consumed by endophytic methanotrophs.…”
Section: Uncertainties and Limitationsmentioning
confidence: 85%
“…This pathway was criticized (e.g. Dueck et al, 2007;Nisbet et al, 2009), and although numerous studies have since confirmed aerobic emissions from plants and better resolved its physical drivers (Fraser et al, 2015), global estimates still vary by 2 orders of magnitude meaning any potential implication for the global methane budget remains highly uncertain. Second, plants act as "straws", drawing methane produced by microbes in anoxic soils (Rice et al, 2010;Cicerone and Shetter, 1981).…”
Section: Vegetationmentioning
confidence: 99%
“…In particular, CH 4 formation and emissions by both dead and living plants 8 has been intensely discussed in recent years 1,13,14 . It has been shown that CH 4 can be produced abiotically from plant material by exposing it to ultraviolet (UV) irradiation [15][16][17][18] .…”
mentioning
confidence: 99%